2013
DOI: 10.1159/000354758
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cytomegalovirus Infection in Pregnant Egyptian Women Confirmed by Cytomegalovirus IgG Avidity Testing

Abstract: Objective: To determine the frequency of primary cytomegalovirus (CMV) infection in pregnant Egyptian women using CMV IgG avidity testing. Subjects and Methods: A cross-sectional study was conducted at Suez Canal University Hospital, Ismailia, Egypt. A total of 546 pregnant women, presenting for routine antenatal screening, were tested for CMV IgG and IgM using a commercially available enzyme-linked immunosorbent assay (ELISA). Sera from CMV IgM-positive women were tested by CMV IgG avidity assay. Results: All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
3
22
2
1
Order By: Relevance
“…In Egypt, a recent study reported the prevalence of IgG to be 100% and 7.3% for IgM. All samples with positive IgM in this study had a high AI (15).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In Egypt, a recent study reported the prevalence of IgG to be 100% and 7.3% for IgM. All samples with positive IgM in this study had a high AI (15).…”
Section: Discussionsupporting
confidence: 49%
“…Precedent study from Egypt revealed high rates of positive serological tests for HCMV between pregnant women (15).…”
Section: Introductionmentioning
confidence: 99%
“…Many laboratories using CMV IgG avidity to discriminate primary from nonprimary CMV infection follow a reflexive algorithm whereby only CMV IgG-positive samples that are also CMV IgM positive are tested for CMV IgG avidity (6,17,18,31,34,48,58); yet, investigators that have tested all CMV IgG-positive samples for avidity, regardless of the CMV IgM result, have consistently found that 1% to 3% of IgG-positive, IgMnegative samples exhibit low IgG avidity (16,48,57), suggesting an increased risk of intrauterine transmission. Indeed, transmission has been documented in patients who lacked CMV IgM but exhibited low IgG avidity (14,61); it is likely that these women were in the narrow time window when IgM reversion has occurred but avidity is still low (3,(28)(29)(30)(31).…”
Section: How Should Intermediate CMV Igg Avidity Results Be Used?mentioning
confidence: 99%
“…Studies assessing CMV IgG avidity showed that low CMV IgG avidity is both a sensitive and a specific marker of primary CMV infection (1-3). Indeed, CMV IgG avidity is increasingly considered the "gold standard" for distinguishing primary from nonprimary CMV infection (1,11,12,16) and is being used worldwide to identify primary CMV infection during pregnancy (14,(17)(18)(19)(20)(21).…”
Section: Ongenital Cytomegalovirus (Cmv) Infection Is the Most Commmentioning
confidence: 99%
See 1 more Smart Citation